Comparison of Effectiveness of Maitland’s Mobilizations at End-Range Versus Within Pain-Free Joint Range of Movement in Treatment of Patients with Frozen Shoulder RCT (British Journal of Multidisciplinary and Advanced Studies, 2023)
Maitland’s mobilizations are an important treatment option for treating patients with Frozen shoulder or Adhesive capsulitis of shoulder joint. In this study we compared the efficacy of Maitland’s mobilization at end-range of tissue resistance with high intensity glides i.e. High Grade with low intensity glides i.e. Low grade within pain free range of joint movement. The study was conducted at OPD of Department of Physical Therapy, Mayo Hospital, Lahore. In this study total of 57 patients were taken and only 36 patients were selected after assessing on inclusion criteria. Those 36 patients were divided into 3 groups with 12 patients in individual group. With the joint close to its neutral position, translation and distraction techniques were used to begin mobilization techniques in the fundamental starting positions. Numeric Pain Rating Scale (NPRS) and SPADI scales were used for measuring pain and disability index. ROMs were measured before, during and after treatment course i.e. at Day 1, after 2 weeks and after 4 weeks respectively. Statistical analysis was done on SPSS using ANOVA. When the ranges were compared by using ANOVA on SPSS it was evident that Group A patients showed better treatment outcomes as compared to other two groups. P-value (0.000) less than 0.05 is considered significant for group A patient. Mean of demographic data also support the fact that AC is more common in women than man. As a result of this study we can conclude that all treatment options gave good results in enhancing range of motion (ROM) and decreasing pain in shoulder joint but high-grade mobilization techniques applied at end range gave a significant treatment outcome on Ranges when compared. Numeric Pain Rating Scale (NPRS) and SPADI scales